由
引理 1.3.18,存在
\(f_i(x)(i=1,\dots ,m)\),使得对任意
\(i,j=1,\dots ,m\)且
\(i\neq j\),都有
\begin{equation}
f_i(x)=l_i(x)p_i(x)+1,\quad f_i(x)=h_{ij}(x)p_j(x).\tag{1.3.7}
\end{equation}
令
\(f(x)=\sum\limits_{i=1}^m f_i(x)g_i(x)\),将
(1.3.7)代入得
\begin{equation*}
\begin{array}{ccl}
f(x)&=&f_i(x)g_i(x)+\sum\limits_{j\neq i,j=1}^m f_j(x)g_j(x)\\
&=&\left[g_i(x)l_i(x)p_i(x)+g_i(x)\right]+\sum\limits_{j\neq i,j=1}^m\left[h_{ji}(x)p_i(x)\right]g_j(x)\\
&=&p_i(x)\left[g_i(x)l_i(x)+\sum\limits_{j\neq i,j=1}^m h_{ji}(x)g_j(x)\right]+g_i(x).
\end{array}
\end{equation*}
根据带余除法,存在\(q(x),g(x)\in\F[x]\),使得
\begin{equation*}
f(x)=\left[\prod\limits_{i=1}^m p_i(x)\right]q(x)+g(x),
\end{equation*}
其中\(\deg g(x)< \deg \left[\prod\limits_{i=1}^m p_i(x)\right]=\sum\limits_{i=1}^m \deg p_i(x)\)。则
\begin{equation*}
g(x)=p_i(x)\left[g_i(x)l_i(x)+\sum\limits_{j\neq i,j=1}^m h_{ji}(x)g_j(x)-q(x)\prod\limits_{j\neq i,j=1}^m p_j(x)\right]+g_i(x).
\end{equation*}
记\(q_i(x)=g_i(x)l_i(x)+\sum\limits_{j\neq i,j=1}^m h_{ji}(x)g_j(x)-q(x)\prod\limits_{j\neq i,j=1}^m p_j(x)\),则
\begin{equation*}
g(x)=p_i(x)q_i(x)+g_i(x).
\end{equation*}
再证明唯一性。若存在\(g(x),h(x)\in\F[x]\),使得
\begin{equation*}
g(x)=p_i(x)q_i(x)+g_i(x),\ h(x)=p_i(x)t_i(x)+g_i(x),
\end{equation*}
且\(\deg g(x)< \sum\limits_{i=1}^m\deg p_i(x),\deg h(x)< \sum\limits_{i=1}^m\deg p_i(x)\)。则
\begin{equation*}
g(x)-h(x)=p_i(x)\left[q_i(x)-t_i(x)\right],
\end{equation*}
即\(p_i(x)| g(x)-h(x)\)。注意到\(p_1(x),p_2(x),\cdots ,p_m(x)\)两两互素,所以
\begin{equation*}
\prod\limits_{i=1}^m p_i(x)| g(x)-h(x).
\end{equation*}
而
\begin{align*}
\deg\left[g(x)-h(x)\right]&\leq\max\{\deg g(x),\deg h(x)\} \\
&< \sum\limits_{i=1}^m\deg p_i(x) \\
&=\deg\left[\prod\limits_{i=1}^m p_i(x)\right],
\end{align*}
故\(g(x)-h(x)=0\),即此时\(g(x)\)是唯一的。